Application progress of RVG peptides to facilitate the delivery of therapeutic agents into the central nervous system. Issue 15 (24th February 2021) - Wang, Qinghua; Cheng, Shang; Qin, Fen; Fu, Ailing; Fu, Chen
Abstract : Rabies virus glycoprotein (RVG) peptides have been developed to deliver drugs for CNS diseases. In the present review, RVG-mediated drug delivery systems are summarised, which can deliver almost all small molecules and macromolecule agents. Abstract : The incidence of central nervous system (CNS) diseases is increasing with the aging population. However, it remains challenging to deliver drugs into the CNS because of the existence of a blood–brain barrier (BBB). Notably, rabies virus glycoprotein (RVG) peptides have been developed as delivery ligands for CNS diseases. So far, massive RVG peptide modified carriers have been reported, such as liposomes, micelles, polymers, exosomes, dendrimers, and proteins. Moreover, these drug delivery systems can encapsulate almost all small molecules and macromolecule drugs, including siRNA, microRNAs, DNA, proteins, and other nanoparticles, to treat various CNS diseases with efficient and safe drugs. In this review, targeted delivery systems with RVG peptide modified carriers possessing favorable biocompatibility and delivery efficiency are summarized.